Analisis Motivasi Siswa SMA dalam Membangun Jiwa Kewirausahaan - Pangondian Gultom (Medan Resource Center, 2021)
The writing of this article aims to see how the motivation of teachers, parents, social environment provides a significant impetus in building an entrepreneurial spirit. Based on the literature review that has been carried out from the results of previous studies, it shows that the role of the teacher in providing motivation for students is very positive and significant in building the entrepreneurial spirit of students. In addition, the role of parents also shows positive and significant things. Where parents become role models for their children to become entrepreneurs. Finally, it is followed by the influence of the social environment in which students socialize. Some of the research results found also show that the environment where students socialize and exchange information has a positive impact on the development of the entrepreneurial spirit of high school students.